2011
DOI: 10.2319/091210-532.1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between temporomandibular joint disk displacement and mandibular asymmetry in skeletal Class III patients

Abstract: Objective: To investigate the relationship between temporomandibular joint disk displacement (TMJ DD) and facial asymmetry in skeletal Class III patients. Materials and Methods: The subjects comprised 97 skeletal Class III adult patients seeking orthodontic treatment. In addition to the routine lateral and posteroanterior (PA) cephalograms, and regardless of the TMJ status, each subject consented to magnetic resonance imaging (MRI) to evaluate their TMJs. According to MRI readings, subjects were classified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…Facial asymmetry (FA) might arise from some pathological conditions that affect TMJ, such as congenital disorders, 14 internal derangements, 15 rheumatoid arthritis 16 and osteoarthritis 17 . For this reason, the relation between TMJ disorders and craniofacial morphology has been extensively studied 18‐23 . FA refers to a state of lack of equity between the right and left side structures, divided by the median sagittal plane, 24 which may impact facial aesthetic and attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Facial asymmetry (FA) might arise from some pathological conditions that affect TMJ, such as congenital disorders, 14 internal derangements, 15 rheumatoid arthritis 16 and osteoarthritis 17 . For this reason, the relation between TMJ disorders and craniofacial morphology has been extensively studied 18‐23 . FA refers to a state of lack of equity between the right and left side structures, divided by the median sagittal plane, 24 which may impact facial aesthetic and attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral TMJ ID displays a deviation of mention to the affected side [ 28 , 29 , 31 ]. And reverse examination study also demonstrated positive correlations between short ramus and condyle as well as deviated mention being associated with TMJ disc displacement and derangement [ 32 , 33 ]. Thus, the severity of TMD and disc displacement can lead to mandibular hypoplasia or facial asymmetry [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Concurrently, temporomandibular disorders have been demonstrated to induce mandibular asymmetry. [7][8][9][10] A study conducted by Emshoff et al, 11 has shown that TMJ disc displacements without reduction and osteoarthrosis are important determinants of mandibular backward positioning. Disc displacement might induce skeletal changes in facial morphology.…”
Section: Introductionmentioning
confidence: 99%